Legal Certainty for Photo Creators against Unauthorized Uploading on E-commerce based on the Copyright Law - Hannin Pradita Nur Soulthoni (Unnes Law Journal, 2024)
In the contemporary landscape of digital commerce, the phenomenon of unauthorized use of copyrighted materials, especially photographs, poses significant challenges. This study delves into the realm of intellectual property rights, particularly focusing on copyright regulations, licensing, and legal protection concerning photographic content within e-commerce platforms. The research adopts a normative legal approach to analyze existing laws related to copyright regulation and protection in the context of product sales on e-commerce platforms. It is characterized by a descriptive-analytical methodology aimed at elucidating and analyzing legal regulations governing copyright, licensing, and legal certainty within the e-commerce environment. The findings reveal crucial insights into the legal certainty provided by copyright laws, emphasizing the significance of legal protection for creators and innovators in the digital age. Despite advancements, the study identifies persistent challenges, such as the widespread unauthorized use of photographic content in e-commerce settings, leading to infringements on intellectual property rights. The analysis highlights pertinent legal provisions within Indonesian copyright laws, outlining the rights and protections afforded to creators of photographic works. It underscores the importance of legal enforcement and the role of stakeholders, including businesses, e-commerce platforms, and governmental authorities, in upholding intellectual property rights. In conclusion, the research underscores the imperative of enhancing legal frameworks, enforcement mechanisms, and stakeholder collaboration to safeguard intellectual property rights in the digital era. By elucidating legal complexities and proposing strategies for compliance and enforcement, this study contributes to advancing the discourse on intellectual property protection within the digital commerce landscape.